Clinical heterogeneity in Fabry disease: A clinical case - Assel Issabekova; Olga Mashkunova (National Scientific Medical Center, 2023)
Fabry disease is an orphan lysosomal storage disease characterized by progressive organ damage. Considering that the disease is rare, the low awareness of doctors about this pathology leads to late diagnosis of the disease and untimely pathogenetic therapy. Clinical case of late (relative to clinical manifestation) diagnosis of the "classical" phenotype of Fabry Disease in a male patient with cardiac and renal damage and typical early presentations such as neuropathic pain, angiokeratomas, hypohidrosis.